Consensus research priorities for paediatric status epilepticus: A Delphi study of health consumers, researchers and clinicians. (March 2018) - Furyk, Jeremy; Ray, Robin; Watt, Kerriane; Dalziel, Stuart R.; Oakely, Ed.; Mackay, Mark; Dabscheck, Gabriel; Riney, Kate; Babl, Franz E.
Highlights: A Delphi process was conducted with experts in paediatric status epilepticus. 9 consensus high priority questions were identified. Future research efforts should be directed towards these priority areas. Abstract: Purpose: Status epilepticus (SE) is a paediatric emergency with significant morbidity and mortality. Recommendations beyond first line care are not based on high quality evidence. Emergency physicians and neurologists are key stakeholders in managing this condition. A collaborative, widely consulted approach to identifying priorities can help direct limited research funds appropriately. The objectives of this study are to identify consensus research priorities in paediatric SE among experts and health consumers. Methods: A three-stage Delphi process was conducted. Paediatric Neurologists and Emergency Physicians in Australia and New Zealand participated. Round one asked participants to generate three research questions important for further research in paediatric status epilepticus. Responses were refined into unique individual questions. Rounds two and three required participants to rate questions on a seven point ordinal scale. Health consumers were invited to participate by providing up to three problem areas that could be addressed by research. Results: 54 experts and 76 health consumers participated in the process. Nine questions reached our definition of consensus "high priority", 21 questions achieved consensus "low priority" and seven questions did not achieve consensus. High priority areas included second line management including levetiracetam (efficacy, dose and timing), use of third line agents, induction of anaesthesia (timing and best agent), management of focal SE, and indicators of "subtle SE". Consumer priority areas included themes of treatment efficacy, aetiology, and community education. Conclusion: We identified nine priority research questions in paediatric SE, congruent with the health consumer theme of treatment efficacy. Future research efforts should be directed towards these priority areas.